The Conundrums of MBA Rankings - Betti, Ricardo (International Higher Education, 2010)
The MBA Rankings do not offer prospective candidates much help in making informed choices about preferred programs. The rankings are inconsistent with one another; users should understand what is being measured by each different rankings and use them only as supplemental sources. Given the extensive differences among the available rankings, readers would better spend their time analyzing the ranking criteria before making any valid inferences based on this superficial quality measurement.